Jewish Moroccan folk narratives from Israel - Bar-Yitsḥaḳ, Ḥayah; Shenhar-Alroy, Aliza; Widmann, Miriam (Raphael Patai Series in Jewish Folklore and Anthropology, 2018)
Jewish Moroccan Folk Narratives focuses on two central elements: textual research to examine the aesthetic qualities of the narrative, their division into genres, the various versions and their parallels, and acculturation in Israel, as well as contextual research to examine the performance art of the narrator and the role of the narrative as a communicative process in the narrating society. The collection includes twenty-one narratives by twelve storytellers; an account of the narrators' lives and a commentary have been applied to each. In contrast to most anthologies of Jewish folktales, the texts in this book were recorded in the natural context of narration and in the language of origin (Judaeo-Arabic), meeting the most vigorous standards of current folklore scholarship.